Synthetic mimetics assigned a major role to IFNAR2 in type I interferon signaling - Zoellner, Nele; Coesfeld, Noémi; De Vos, Frederik Henry; Denter, Jennifer; Xu, Haifeng C.; Zimmer, Elena; Knebel, Birgit; Al-Hasani, Hadi; Mossner, Sofie; Lang, Philipp A.; Floss, Doreen M.; Scheller, Jürgen (Frontiers in Microbiology, 2022)
Type I Interferons (IFNs) are potent inhibitors of viral replication. Here, we reformatted the natural murine and human type I Interferon-α/β receptors IFNAR1 and IFNAR2 into fully synthetic biological switches. The transmembrane and intracellular domains of natural IFNAR1 and IFNAR2 were conserved, whereas the extracellular domains were exchanged by nanobodies directed against the fluorescent proteins Green fluorescent protein (GFP) and mCherry. Using this approach, multimeric single-binding GFP-mCherry ligands induced synthetic IFNAR1/IFNAR2 receptor complexes and initiated STAT1/2 mediated signal transduction via Jak1 and Tyk2. Homodimeric GFP and mCherry ligands showed that IFNAR2 but not IFNAR1 homodimers were sufficient to induce sustained STAT1/2 signaling. Transcriptome analysis revealed that synthetic murine type I IFN signaling was highly comparable to IFNα4 signaling and resulted in efficient elimination of vesicular stomatitis virus (VSV) in a cell culture based viral infection model using MC57 cells stimulated with synthetic type IFN ligands. Using intracellular deletion variants and point mutations, Y510 and Y335 in murine IFNAR2 were verified as unique phosphorylation sites for STAT1/2 activation, whereas the other tyrosine residues in IFNAR1 and IFNAR2 were not involved in STAT1/2 phosphorylation. Comparative analysis of synthetic human IFNARs support this finding. In summary, our data showed that synthetic type I IFN signal transduction is originating from IFNAR2 rather than IFNAR1.